1978
DOI: 10.1021/jm00202a002
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of antimalarial agents via complex formation with .alpha.-(2,4,5,7-tetranitro-9-fluorenylideneaminooxy)propionic acid

Abstract: The resolution of several antimalarial agents via pi-complex formation with alpha-(2,4,5,7-tetranitro-9-fluorenylideneaminooxy) propionic acid (TAPA) is reported. Since this represents the first use of this agent for the resolution of amines, some details of the separations are presented. The method proved successful for resolving weakly alkaline amines that did not form stable salts with common resolving acids, highly insoluble amines that did not form soluble salts with usual resolving acids, and amines that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1978
1978
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…PQ was resolved to (+)-(S)-and (2)-(R)-forms at NCNPR, their identity and purity were confirmed by spectral data (infrared, NMR and high-resolution MS), and their physical data (mp, [alpha]D) were compared with published values (Carroll et al, 1978). We prepared cPQ using the procedure reported by McChesney and Sarangan (1984).…”
Section: Methodsmentioning
confidence: 99%
“…PQ was resolved to (+)-(S)-and (2)-(R)-forms at NCNPR, their identity and purity were confirmed by spectral data (infrared, NMR and high-resolution MS), and their physical data (mp, [alpha]D) were compared with published values (Carroll et al, 1978). We prepared cPQ using the procedure reported by McChesney and Sarangan (1984).…”
Section: Methodsmentioning
confidence: 99%
“…This produced almost 200 PQ derivatives (Tables 2-4) bearing diverse groups in one or more given positions of the ring [6,46,[161][162][163][164][165][166][167][168][169][170][171][172][173][174][175][176][177][178][179]. Globally, the most favourable substituent insertions towards anti-malarial activity where those of methyl groups at positions 4 and 2, tert-butyl at position 2, simultaneous insertion of ethyl substituents at positions 2 and 4 and pentyloxy at position 5, as well as insertion at position 5 of alkoxy, fluoro, and 3-or 4-substituted phenoxy groups [51,163].…”
Section: Modifications At the Quinoline Ringmentioning
confidence: 99%
“…1). Limited previous results comparing the individual enantiomers of PQ, made available by a challenging and expensive resolution of racemic PQ (12), also suggested different therapeutic indices and rate of metabolism. Schmidt et al (13) reported that (Ï©)-(S)-PQ, (ÏȘ)-(R)-PQ, and racemic PQ ( Fig.…”
mentioning
confidence: 99%
“…A major impediment to such clinical evaluation was the lack of availability of PQ enantiomers of cGMP quality. The cumbersome nature of the method previously used to resolve PQ (12) would not provide the enantiomers economically nor scale appropriately for cGMP preparation. To overcome this limitation and to provide PQ enantiomers economically, we have developed a simple procedure to resolve racemic PQ on a large scale.…”
mentioning
confidence: 99%